Role of thrombocytopenia in risk stratification for acute kidney injury after living donor liver transplantation - Jaesik Park; Jangsu Jeong; Ho Joong Choi; Jung-Woo Shim; Hyung Mook Lee; Sang Hyun Hong; Chul Soo Park; Jong Ho Choi; Min Suk Chae (Platelets, 2021)
The aim of our study was to investigate pre and intraoperative clinical factors, including platelet count, which could inform risk stratification of early acute kidney injury (AKI) after living donor liver transplantation (LDLT). Additionally, the impact of severe thrombocytopenia on AKI risk was assessed using a propensity score (PS)-matched analysis. In total, 591 adult patients who underwent LDLT between January 2009 and December 2018 at our hospital were retrospectively analyzed. Early postoperative AKI was determined based on the KDIGO criteria, and 149 patients (25.2%) developed AKI immediately after surgery. In a multivariate analysis, a lower preoperative platelet count was significantly associated with early postoperative AKI, together with diabetes mellitus, lower hourly urine output, and longer graft ischemic time; furthermore, a decrease in platelet count was correlated with AKI severity. After adjusting for the PS, the probability of AKI was significantly (1.9-fold) higher in patients with severe thrombocytopenia than in those without severe thrombocytopenia. Patients with thrombocytopenia showed a higher postoperative incidence of AKI and a higher requirement for dialysis than those without thrombocytopenia. The platelet count can easily be obtained via regular blood analysis of patients scheduled for LDLT and can be used to identify patients at risk for AKI.